STRESS AND QUALITY OF LIFE PATIENTS WITH DIABETES MELLITUS - Duma Ayu Sianturi; Agustina Boru Gultom (Jurnal Kesehatan Tambusai, 2023)
Diabetes Mellitus is still a health issue both globally and in Indonesia. This is evidenced by the increasing morbidity and can even lead to a decrease in the quality of life and event death if not handled properly. One of the factors that may be related to the quality of life of patients with diabetes mellitus is stress. This study aimed to analyze the relationship between stress and quality of life of patients with diabetes mellitus at Pirngadi Hospital, Medan City in 2022. The study used an analytical method with a cross-sectional approach. The number of samples was calculated using the formula and 41 patients were taken using purposive sampling technique. The instrument used for stress is the Perceived Stress Scale (PSS) which includes 10 statement items.  As for the quality of life using WHOQOL-BREF as many as 26 statement items.  Both of these instruments were standard instruments that have been tested for validity and reliability. Data analysis was performed using the Chi-square test. It obtained p-value 0.003. It indicated a relationship between stress and the quality of life of patients with diabetes mellitus. It is recommended that the nurse can train the patient some stress reductions methods and encourage the patient to do it every day.